ESTIMATING BACTERIAL POPULATION ON THE PHYLLOSPHERE BY SERIAL DILUTION PLATING AND LEAF IMPRINT METHODS - Yadav, Ram Kailash P.; Kakamanoli, Katerina; Vokou, Despoina (Ecoprint: An International Journal of Ecology, 2011)
The plant phyllosphere constitute a habitat for variety of microorganisms; bacteria are the most common ones. In this study, we assessed the ability of serial dilution plating and leaf imprint methods to elucidate population abundance on the phyllosphere of eight plant species co-occurring in the same area in mediterranean ecosystem (northern Greece). The serial dilution plating method outweighed the leaf imprint method in determining the total epiphytic bacterial population and the estimates were significantly higher. However, the ability to detect presence of bacterial colony on leaf surface is higher for the leaf imprints, suggesting specific use of this method for practical purposes. Key words: Phyllosphere; Bacterial population; Serial dilution plating; Leaf imprint DOI: 10.3126/eco.v17i0.4105 Ecoprint An International Journal of Ecology Vol. 17, 2010 Page: 47-52 Uploaded date: 29 December, 2010